REGULATION HEGEMONY AND ACCOUNTABILITY OF THE LOCAL GOVERNMENT: A STUDY ON REGIONAL FINANCIAL MANAGEMENT IN INDONESIA - Banu Witono; Nurkholis *; Roekhudin * (The International Journal of Accounting and Business Society, 2021)
AbstractObjectives - The purpose of this study is to uncover the reality of implementing regional financial management regulations and their impact on local government accountability.Research method approach - This study uses a critical qualitative research approach to the Gramsci hegemony perspective. This approach is useful for analyzing the shackles of regulation in the implementation of regional financial management.Findings - The results show that regulation has become a means for the state to dominate in the realm of political society and hegemony for civil society. This results in an orientation of local government accountability which tends to vertical accountability rather than horizontal (public) accountability .Practical implications -Ã‚Â  Changes in regional autonomy regulations have led to increasing dominance of the central government to the regions. This is reflected in the various regulations produced by the institutions in the central government which shackle the space and innovation of the local government in managing regional finances.Social implications - Due to the shackles of the regulation, local governments prioritize serving the interests of the central government (vertical accountability) compared to services to the society (horizontal accountability).Originality / Value - This study contributes to uncovering the facts that occur related to regional financial management, so that it can provide input to the government in the implementation of regional government accountability.Keywords: Regional Government Accountability, Regional Financial Management Regulations, Regulation Hegemony.Paper Type: Research Paper